2013
DOI: 10.1097/iae.0b013e3182618be0
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab for Polypoidal Choroidal Vasculopathy in Non-Asian Patients

Abstract: Intravitreal ranibizumab was well tolerated in non-Asian patients with polypoidal choroidal vasculopathy; the majority of eyes experienced improvements in best-corrected visual acuity and center point thickness after ranibizumab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This phenomenon has been found by several studies. [19223435363738394041] Lai et al . [34] reported the efficacy of intravitreal bevacizumab therapy for PCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been found by several studies. [19223435363738394041] Lai et al . [34] reported the efficacy of intravitreal bevacizumab therapy for PCV.…”
Section: Discussionmentioning
confidence: 99%
“…Using ranibizumab (as-needed) therapy, Marcus et al . [38] reported that the mean BCVA increased from baseline by 1.2 Snellen lines at 12 and 24 months. The mean CRT decreased by 53 and 67 μm from baseline at 12 months and 24 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study 7 showed good results with ranibizumab 0.5 mg and overall supports anti-VEGF monotherapy as a viable therapy for non-Asian PCV. The majority of patients with baseline CFT 4300 μm had favorable vision gains and CFT reduction.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] In a previous study 7 (ClinicalTrials.gov identifier: NCT00837330), we evaluated intravitreal ranibizumab 0.3-and 0.5-mg monotherapy in 20 eyes of non-Asian patients with PCV. Ranibizumab (0.3-and 0.5-mg groups pooled) was well tolerated and resulted in improved best-corrected visual acuity (BCVA; +1.2 Snellen lines at months 12 and 24) and reduced center point thickness (−53 and − 67 μm at months 12 and 24, respectively) in the majority of eyes.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of complete regression in polyps was found to be 77.8% with combined treatment, 71.4% with PDT monotherapy, and 28.6% with ranibizumab monotherapy (6,19) A mean of 5 injections were performed in the present study. In a study conducted by Marcus et al (24), a mean of 7.2 injections per eye was administered over a 24-month follow-up period. They observed a 1.2 Snellen letter-increase at month 24 compared with the baseline.…”
Section: Discussionmentioning
confidence: 99%